Too Dense or Not Too Dense: Higher Planting Density Reduces Cannabinoid Uniformity but Increases Yield/Area in Drug-Type Medical Cannabis - Danziger, Nadav; Bernstein, Nirit (Frontiers in Plant Science, 2022)
A major challenge for utilizing cannabis for modern medicine is the spatial variability of cannabinoids in the plant, which entail differences in medical potency. Since secondary metabolism is affected by environmental conditions, a key trigger for the variability in metabolism throughout the plant is variation in local micro-climates. We have therefore hypothesized that plant density, which is well known to alter micro-climate in the canopy, affects spatial standardization and concentrations of cannabinoids in cannabis plants. Canopy density is affected by shoot architecture and by plant spacing, and we have therefore evaluated the interplay between plant architecture and plant density on the standardization of the cannabinoid profile in the plant. Four plant architecture modulations treatments were employed on a 'drug-type’ medicinal cannabis cultivar, under a density of 1 or 2 plants/m2. The plants were cultivated in a naturally lit greenhouse with photoperiodic light supplementation. The results revealed an effect of plant density on cannabinoid standardization, as well as an interaction between plant density and plant architecture on the standardization of cannabinoids, thus supporting the hypothesis. Increasing planting density from 1 to 2 plants/m2 decreased inflorescence yield per plant, but increased yield quantity per area by 28-44% in most architectural treatments. The chemical response to plant density and architecture modulation was cannabinoid specific. Concentrations of cannabinoids in axillary inflorescences from the bottom of the plants were up to 90% lower than at the apical inflorescence at the top of the plant, considerably reducing plant uniformity.. The response of the plants to high density involved enhanced leaf drying at the bottom of the plants, increased plant elongation and reduced cannabinoid concentrations, suggesting an involvement of chronic light deprivation at the bottom of the plants. Therefore, most importantly, under high density architecture treatments that facilitate increased light penetration to the bottom of the plant such as ‘Defoliation’, or that eliminated inflorescences development at the bottom of the plant such as removal of branches from the lower parts of the plant, increased chemical standardization. This study revealed the importance of plant density and architecture for chemical quality and standardization in 'drug-type' cannabis.